The little house of hope [book with audioplayer] - Jennings, Terry Catasús ([Library Ideas, LLC], 2023)
"When Esperanza and her family arrive in the United States from Cuba, they buy a little house, una casita. It may be small, but they soon prove that there's room enough to share with a whole community"--